2005
DOI: 10.1242/jcs.02709
|View full text |Cite
|
Sign up to set email alerts
|

Host and parasite-derived IKK activities direct distinct temporal phases of NF-κB activation and target gene expression followingToxoplasma gondiiinfection

Abstract: Activation of NF-κB by the intracellular pathogen Toxoplasma gondii is associated with the localization of phosphorylated IκBα to the parasitophorous vacuole membrane (PVM). This is mediated by a parasite-derived IκB kinase (TgIKK) activity and is independent of host IKK function. In the present study, we examined the roles of host IKK and parasite-derived TgIKK on the temporal modulation of NF-κB activation. Despite the presence of TgIKK activity at the PVM, nuclear translocation of NF-κB and subsequent gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 44 publications
3
56
0
Order By: Relevance
“…Activation of NF-κB is partially achieved by phosphorylation of a subset of host IκBα [21]. However, it soon became clear that manipulation of the NF-κB pathway is more complex [22]. To address this issue, we developed a stable NF-κB-GFP reporter cell line (PSH2) for screening of mutants of the T. gondii that fail to activate NF-κB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of NF-κB is partially achieved by phosphorylation of a subset of host IκBα [21]. However, it soon became clear that manipulation of the NF-κB pathway is more complex [22]. To address this issue, we developed a stable NF-κB-GFP reporter cell line (PSH2) for screening of mutants of the T. gondii that fail to activate NF-κB.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that activation of NF-κB is partially achieved by phosphorylation of a subset of host IκBα [21]. However, it soon became clear that manipulation of this pathway is a complex process involving multiple elements [22], which lead us to develop the reporter cell line system to screen for NF-κB defective mutants of the parasite.…”
Section: Introductionmentioning
confidence: 99%
“…Cells depleted of IKKα/β are incapable of activating NFκB. Although the IKKβ subunit is the main player in the phosphorylation of IκBα, the IKKα subunit is also required to induce the expression of genes targeted by NF-κB [108]. Notably, T. gondii infected cells present a striking increase in phosphorylated IκBα (PIκB) concentrated at the PVM [99].…”
Section: Role Of the Nf-κb Pathwaymentioning
confidence: 99%
“…The contribution of parasite TgIKK in the activation of the NF-κB pathway by infection was investigated recently by Molestina et al [108]. They showed that while the host IKK signalosome is essential for translocating NF-κB to the nucleus and for the observed upregulation of NF-κB target genes early after T. gondii infection, maintenance of the response appears to require the contribution of parasite TgIKK during the intermediate phase of the infection at a stage where host IKK dampening is normally seen.…”
Section: Role Of the Nf-κb Pathwaymentioning
confidence: 99%
“…The target amount was normalized to an endogenous reference and relative to a calibrator (fold differences), is given by 2-CT. Using the expression level of target genes in the control tissue as a base line, the expression folds have been detected in the treated ones assuming that both standard and target have same efficiencies (Molestina and Sinai, 2005). Threshold cycle values (Ct) were used, as Ct indicates the PCR cycle number at which the amount of amplified target reaches a fixed threshold in order to convert threshold cycles in copy numbers.…”
Section: Quantification Of the Targeted Genes Using The Real-time Pcrmentioning
confidence: 99%